Share repurchases: Which number of shares should be used by JSE-listed companies when publishing market capitalisation in annual reports? - P. G. Bester; W. D. Hamman; L. M. Brummer; N. Wesson; B. W. Steyn-Bruwer (South African Journal of Business Management, 2008)
The legalisation of share repurchases in South Africa since July 1999 introduced additional complexity to financial reporting. The repurchasing of shares by subsidiaries or share trusts has led to a new concept: the number of company shares differs from the number of group shares. Ratios like earnings per share and headline earnings per share are governed by accounting standards and circulars, and prescribe the use of the (weighted) number of group shares. No guidance exists on the calculation of market capitalisation.This article aims to determine the methods used by companies listed on the JSE Securities Exchange South Africa (JSE) to calculate their number of shares when publishing market capitalisation. It was found that only about 25% of companies participating in share repurchases and publishing market capitalisation in their annual reports calculated market capitalisation based on the number of group shares. About 75% of the companies did not calculate their market capitalisation based on the number of group shares (i.e. they omitted to deduct subsidiary repurchases and/or trust consolidations in their calculation of the number of shares). It was also found that the JSE, when compiling the Top 40 index, calculates market capitalisation based on the number of company shares (i.e. ignoring subsidiary repurchases and trust consolidations). Accounting guidance is needed on the reporting of market capitalisation to ensure that this aspect is not overstated by the reporting entities.
Keywords: 650